Bata Bertulis Kaitannya dengan Bangunan Candi 1 Bumiayu - Retno Purwanti (Balai Arkeologi Yogyakarta, 1994)
Of a number of inscriptions that have been found in Indonesia, some of which were found in Palembang and its surroundings. These inscriptions are usually associated with the existence of the Srivijaya kingdom. Archaeological remains in the form of temple building remains were found in Bumiayu Village, Perwakilan Tanah Abang District, Muara Enim Regency, South Sumatra Province. Identification of the dating of Candi 1 can also be seen from the findings of inscriptions and bricks inscribed with ancient Javanese letters. In 1991 a gold plate was found from inside a jar around the site of Candi 1. In addition, in 1993 found a fragment of the inscription etched on the brick, consisting of three rows. Based on the paleography of the written sources from the 10-12 century AD.